Living conditions and access to health services by Bolivian immigrants in the city of São Paulo, Brazil - Cássio Silveira; Nivaldo Carneiro Junior; Manoel Carlos Sampaio de Almeida Ribeiro; Rita de Cássia Barradas Barata (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2013)
Bolivian immigrants in Brazil experience serious social problems: precarious work conditions, lack of documents and insufficient access to health services. The study aimed to investigate inequalities in living conditions and access to health services among Bolivian immigrants living in the central area of São Paulo, Brazil, using a cross-sectional design and semi-structured interviews with 183 adults. According to the data, the immigrants tend to remain in Brazil, thus resulting in an aging process in the group. Per capita income increases the longer the immigrants stay in the country. The majority have secondary schooling. Work status does not vary according to time since arrival in Brazil. The immigrants work and live in garment sweatshops and speak their original languages. Social networks are based on ties with family and friends. Access to health services shows increasing inclusion in primary care. The authors conclude that the immigrants' social exclusion is decreasing due to greater access to documentation, work (although precarious), and the supply of health services from the public primary care system.